Light‐Mediated Carboxylation Using Carbon Dioxide - Fan, Zhengning; Zhang, Zeyu; Xi, Chanjuan (ChemSusChem, 2020)
Carbon dioxide is a green and sustainable one‐carbon source, which could be utilized in the production of various fine chemicals. In recent studies, the light‐mediated carboxylation employing CO2 has received considerable attention. The photocarboxylation of substrates with CO2 to build novel C−C bonds is introduced in this Minireview. The article is arranged based on the light‐driven reactive intermediates, including CO2 radical anion, substrate radical anions, carbanions, and M−C species. Most of the cases are under the topic of photoredox catalysis, with single electron transfer as the main driving force. Some non‐catalytic examples are also discussed to provide more mechanistic insights. Photocarboxylation: Fixation of CO2 into organic molecules with C−C bond formation is a challenging project. With UV/visible light assistance, alkenes, alkynes, organometallic reagents, organic halides, and sp3 C−H bonds are successfully transformed to the corresponding carboxylic acids. These protocols exhibit divergent chemo‐ and regioselectivity with tolerating broad functional group.